Utilizing technology to enhance laboratory–client interaction while encouraging best behavior. (May 2021) - Woodard, Katie; Kraft, Jordan; Adhikari, Shiva; Patanroi, Daniel; Crim, Bret; Berghefer, Randy; Main, Rodger
As client interactions with veterinary diagnostic laboratories have evolved, so have client expectations: faster results, enhanced accessibility to cases, and more seamless data transfer from the laboratory database; all of these factors have encouraged the evolution of diagnostic laboratory systems. This evolution started with 24-h access to laboratory results via the web, yet data quality remained at the mercy of the person filling out the form. If bad (incomplete) information was flowing in, then the data coming out was equally bad (incomplete or inconsistent). By designing a web-based system integrated into our existing reporting platform, the Iowa State University Veterinary Diagnostic Laboratory (ISU-VDL) set out to improve the quality of submission data by including the premises identification number (PIN) and obtaining consistent location data, all while presenting to the client an easy-to-use interface. Efforts continued by incentivizing the use of this tool and client submission practices. As clients transitioned, data have become more complete, resulting in easier queries and an improved ability to leverage the diagnostic data. To further enhance the client experience, a streamlined daily reporting summary was designed to communicate laboratory results succinctly. The use of these web-based tools had a positive impact on the quality and consistency of the diagnostic data. As new ideas develop, the ISU-VDL strives to foster continuous improvement and positively impact the clients' experience.